Quality of Life in Maintenance Hemodialysis; Stakeholders’ Perspectives – A Qualitative Inquiry (International Journal of Nursing Education, 2021)
Quality of life is a major concept in the arena of healthcare, especially in chronic diseases. ESRDpatients undergoing maintenance hemodialysis experience unique issues involving varying aspects.Using a qualitative approach, the current study explored the perspectives of stakeholders on qualityof life. Thematic analysis done and three major themes - Dialysis - the life line, Global impact of thedisease and strategies to be made, were emerged. Quality of life in hemodialysis patients is markedlyimpaired due to a variety of factors and a comprehensive and tailored approach will be beneficial.